Penciptaan Karya Tari Ledak Manis - Ida Ayu Larasathi Putri Yudistira; Ida Ayu Wayan Arya Satyani; Made Ayu Desiari (Jurnal IGEL : Journal Of Dance, 2026)
Ledak Manis Dance Work is a contemporary dance piece inspired by the phenomenon of love bombing in romantic relationships, a form of emotional manipulation that is often perceived as normal but has serious psychological impacts on women. The creation of this work aims to present a medium of expression, reflection, and education through contemporary dance in order to reveal the phenomenon of love bombing, raise awareness of unhealthy relationship dynamics, and represent the process of recovery and self-awareness of women from emotional manipulation.The creative process employs the Angripta Sasolahan method, which consists of the stages of ngarencana (concept planning), nuasen (thematic immersion and emotional exploration), makalin (movement exploration and development), nelesin (structuring the choreographic composition), and ngebah (final presentation). This method allows the development of concepts, movement exploration, and artistic presentation to proceed in a systematic and structured manner The resulting work is a contemporary dance piece structured into four dramatic phases: falling in love, emotional attachment, psychological destruction caused by manipulation, and awakening toward self-awareness. The performance involves seven dancers, with one dancer portraying the main character and six dancers representing the emotional states of the protagonist. The choreography features dynamic and expressive movement exploration, combined with MIDI (musical instruman digital interface), bold minimalist makeup, and Romantic Playful (romantic feminime and playful contemporary styled costumes. The use of properties such as a wardrobe, rose flowers, and spherical lamps serves as symbols of inner space, fragile love, and hope, thereby strengthening the overall emotional and visual meaning of the performance. Keywords: Ledak Manis, love bombing, Angripta Sasolahan, contemporary